Jack of Fables. [2], Jack of Hearts - Willingham, Bill (Vertigo/DC Comics, 2007)
Jack reveals the secret of his former relationship with the illustrious Snow Queen -- when he took her powers and became known as Jack Frost. In present times, he lands in Las Vegas and meets his lovely new bride, a directionless heiress. Could it possibly be "happily ever after" at last?